Predicting AIDS-induced behavioral change in the general population of young people - Ajduković, Dean (Array, 1992)
Sets individual-psychological and sociodemographic variables for predicting self-reported AIDS-relevant behavioral change were examined. The self-completing questionnaire used in the study contained scales of knowledge and attitudes about AIDS, sex and drug abuse experience scales, and six behavioral change scales. It was anonymously administrated to 2, 655 young people of both sexes, 15-30 years of age, living in 18 cities and towns, regularly employed or attending school. The overall level of knowledge was high and attitudes moderately liberal. Regression analyses showed that only a small fraction of variance in any of the six behavioral change criteria (sex, drugs, personal concern, chance of contracting the disease, desire for more knowledge, and nonfunctional practices) could be attributed to the four predictors presumed to influence the criteria directly (sex risk index, drugs risk index, knowledge, and attitudes). The prediction improved when another 10 variables with assumed indirect influence were included. Socioeconomic status and the drug abuse risk index were most predictive of behavior change. Knowledge and attitudes proved to be poor predictors. It is stressed that the social and cultural specifics in planning prevention must be observed.